Exploring the Expression of Sexual Desire in Ancient Egypt through a Selection of Primary Sources: An Approach from the Emotional Perspective - Garzón Rodríguez, Judit (Aestimatio, 2022)
Sexual desire involves a subjective experience that may differ significantly from one individual to another and is closely linked not only to personal preferences but also to the circumstances of the moment, cultural norms, and social expectations. When experiencing sexual desire, there are not only positive but also negative dynamics at play, and such an experience can also trigger a wide range of emotions that might differ depending on the circumstances of the moment. The aim of this paper is to explore the expression of sexual desire as well as its relationship to a broad spectrum of emotions through a selected group of ancient Egyptian textual sources, such as love songs.